Effects of concertation and size of aqueous QDs on the detection of ionizing radiation based on changes in optical properties. (June 2023) - Assar, Effat; Alehdaghi, Hassan; Azadegan, Behnam; Zare, Hakimeh
Abstract: Colloidal quantum dots (QDs) have recently been used in many applications. In particular, semiconductor and luminescent QDs are suitable candidate for use in optoelectronic devices and optical sensors. The optical properties of aqueous CdTe QDs with high efficiency photoluminescence (PL) make them good candidates for new dosimetry applications. Therefore, comprehensive studies are required of the effects of ionizing radiation on the optical properties of CdTe QDs. In the present study, we investigated the properties of aqueous CdTe QDs by a gamma 60 Co source at different doses. For the first time, we determined the effects of the concentration and size of QDs, which are key factors in a gamma dosimeter. The results demonstrated the concentration-dependent photobleaching property of QDs, which grater changes in the optical properties occurred. The initial size of the QDs affected their optical properties, where red-shifting of PL peak position increased with smaller sizes. Analysis of the effect of gamma irradiation on the thin film QDs indicated that the PL intensity decrease as the dose increased. with increasing dose. X-ray diffraction analysis found no changes in the crystal structure. X-ray photoelectron spectroscopy and Fourier-transform infrared spectroscopy indicated decomposition of the capping agent thioglycolic acid on CdTe QDs after gamma irradiation. Highlights: Optical properties of aqueous CdTe quantum dots (QDs) in gamma dosimeter examined. Effect of size of QDs on optical properties after gamma exposure assessed. Concentrations of QD solutions affected dosimetry properties of CdTe QDs. CdTe QD thin films assessed for use in optical gamma radiation sensors. CdTe QDs are suitable for use in gamma radiation sensors with sensitivity of 50_20 kGy.